Pengaruh Iklan, Kualitas Pelayanan, dan Kepuasan Konsumen terhadap Loyalitas Pelanggan pada E-Commerce Shopee di Masa Pandemi - Lilis Nur Afiah; Budi Prabowo (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
This study aims to determine: (1) the effect of advertising, service quality and customer satisfaction on customer loyalty at E-Commerce Shopee during the pandemic (2) the effect of advertising on customer loyalty at E-Commerce Shopee during the pandemic (3) the effect of service quality on customer loyalty at E-Commerce Shopee during a pandemic (4) the effect of consumer satisfaction on customer loyalty at E-Commerce Shopee during a pandemic. This research method uses quantitative methods. The research sample was taken using purposive sampling method from a total of 100 people taken from the Shopee user population in the Gresik area. The data analysis technique used is multiple linear regression. Based on this research, Fcount is rejected, namely H0, H1 is accepted, so it can be concluded that the independent variables Advertising, Service Quality and Consumer Satisfaction have a significant effect on the dependent variable of Customer Loyalty at Shopee E. -Trade. Users during a Pandemic in the Gresik Region. The results of Tcount Ads H0 are accepted and H1 are rejected, this means that advertisements have no significant effect partially on customer loyalty. The results of Tcount Quality of Service H0 are rejected and H1 is accepted, this means that service quality has a partially significant effect on Customer Loyalty. The results of the Tcount of Consumer Satisfaction H0 are rejected and H1 is accepted, this means that Consumer Satisfaction has a partially significant effect on Customer Loyalty at Shopee E-commerce Gresik Region Keywords: Advertising; Service Quality; Consumer Satisfaction; Customer Loyalty